THE JURIDICAL REVIEW OF LEGAL POWER OF GROSSE DEED AS THE BASIS FOR EXECUTING MORTGAGE EXECUTION AUCTIONS - D Djunaedi; Dwi Wahyono; Setyawati Setyawati (UNISSULA, 2021)
One of the executions of the mortgage object is the sale of the mortgage object through a public auction based on the executorial title contained in the Mortgage Certificate. Before the implementation is carried out by the creditor, a permit (fiat) is required by the local district court. The application for an auction for the execution of mortgage rights through a district court is closely related to obstacles, for example, a lawsuit from a third party (derden verzet) who feels he has the right to the object of execution even though it has nothing to do with creditors and debtors. This opposition made the Chief Justice of the District Court unable to grant the request for execution even though the creditor had a mortgage certificate that was encumbered but was forced to examine the relevant evidence in the trial forum to determine whether the resistance was sufficient reason or just a conspiracy with the debtor to delay the execution. Based on this explanation, the author wants to examine the legal force of the Grosse deed as the basis for the implementation of the mortgage execution auction. The type of research in writing scientific papers is a normative legal research type, with a statutory approach and a legal concept analysis approach (Analytical and Conceptual Approach). The sources of legal materials used in writing this scientific paper came from primary legal materials, secondary legal materials, and tertiary legal materials. The legal materials were collected using library research techniques. Then analyzed using description, systematization, evaluation and finally concluded with argumentation technique. The results of this study are expected to provide scientific knowledge for academics, law enforcers, and the public.